Psihometrične značilnosti De Morton indeksa premičnosti za ocenjevanje premičnosti starostnikov - Zupanc, Aleksander (Rehabilitacija (Ljubljana), 2016)
Background: De Morton mobility index (DEMMI) is a new measurement tool for evaluating mobility, assessing individual performance of fifteen movement items. The purpose of the literature review was to summarise psychometric properties of DEMMI for assessing mobility in older adults. Method: Based on inclusion criteria a literature review was conducted using the PubMed and CINAHL databases. Searching was limited to English language and included all published articles by April 2016. Results: Twelve research articles were included in the review. They included general samples of older adults in acute hospital treatment, in transitional care settings and rehabilitation, older adults with total knee or hip replacement, after hip fracture, with Parkinson's disease and functional independent elderly. In five studies excellent intra- and inter-rater reliability were reported. In 11 studies, construct validity, known-groups validity and high correlation between DEMMI scores and performance-based measurement tools assessing more movement tasks were confirmed. In nine studies, no ceiling or floor effect was reported for DEMMI. Conclusion: DEMMI is a reliable and valid measurement tool, which is able to detect responsiveness of change in older adults in different period of health care and with different causes for mobility inabilities. Due to its included assessing area and according to the confirmed good psychometric properties it would be reasonable to include DEMMI in physiotherapy assessment of mobility in older adults with musculoskeletal impairments and Parkinson's disease.
Keywords: Aged; DEMMI; measurement tools; merilna orodja; mobility; older adults; Physical Therapy Modalities; premičnost; reliability; starostniki; validity; veljavnost; zanesljivost